Infiltrated regulatory T cells and Th2 cells in the brain contribute to attenuation of sepsis-associated encephalopathy and alleviation of mental impairments in mice with polymicrobial sepsis - Saito, Masafumi; Fujinami, Yoshihisa; Ono, Yuko; Ohyama, Shohei; Fujioka, Kazumichi; Yamashita, Kimihiro; Inoue, Shigeaki; Kotani, Joji (Brain, behavior, and immunity, 2021)
•Injection of cecal slurry can induce sepsis and anxiety-like behavior in mice.•Treg and Th2 cell increased in the brain at the chronic phase of sepsis.•Administration of FTY720 delayed recovery of anxiety-like behavior in septic mice.•Infiltrated brain Treg and Th2 cell may attenuate sepsis-associated encephalopathy.•These cells also contribute to the recovery of anxiety in septic mice. Sepsis-associated encephalopathy (SAE) increases not only morbidity and mortality but has been associated with long-lasting mental impairment after hospital discharge in septic patients. Recently, studies have shown that these mental impairments are caused by infection-induced neuroinflammation. However, the role of T cells in the pathogenesis of SAE and mental impairments remains unclear. Thus, in this study, we aimed to clarify how immune cells, especially T cells, influence the development and recovery of these disorders. In the cecal slurry (CS)-induced septic mouse model, we performed three different kinds of behavioral tests, open-field test, marble burying test, and forced swimming test, and observed anxiety-like behavior in septic mice. Additionally, increased interleukin (IL)-1β and IL-6 expression levels, and infiltration of neutrophils and T cells were examined in the brain of septic mice, 10 days after sepsis onset. Twenty days after sepsis onset, the septic mice could recover the number of astrocytes. At day 30, expression levels of IL-1β and tumor necrosis factor (TNF)-α returned to normal levels in the cerebral cortex of septic mice. Interestingly, resolution of neuroinflammation and alleviation of depression were delayed in septic mice treated with FTY720, which inhibits sphingosine-1-phosphate (S1P)-dependent lymphocyte egress from lymph nodes. On analyzing the brain T cells with or without FTY720 in septic mice, the FTY720 untreated mice presented increased regulatory T cells (Treg) and Th2 cells in the brain, whereas the FTY720 treated mice demonstrated increased Th17 in the brain at day 30. Furthermore, in FTY720 treated septic mice, the number of astrocytes in the cerebral cortex remained reduced at day 30. These results suggest that infiltrated Treg and Th2 cells contribute to the attenuation SAE and alleviate SAE-induce mental disorder by resolving neuroinflammation in the chronic phase of sepsis.